2020
DOI: 10.3390/molecules25204772
|View full text |Cite
|
Sign up to set email alerts
|

Association of Moderate Beer Consumption with the Gut Microbiota and SCFA of Healthy Adults

Abstract: Fermented alcoholic drinks’ contribution to the gut microbiota composition is mostly unknown. However, intestinal microorganisms can use compounds present in beer. This work explored the associations between moderate consumption of beer, microbiota composition, and short chain fatty acid (SCFA) profile. Seventy eight subjects were selected from a 261 healthy adult cohort on the basis of their alcohol consumption pattern. Two groups were compared: (1) abstainers or occasional consumption (ABS) (n = 44; <1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…As β-diversity was observed only after 30 days of treatment, the authors hypothesized that the effect on gut microbiota could depend on polyphenols and phenolic acids [ 111 ]. Similar results were obtained in an observational study, especially for higher butyric acid concentration in consumers versus non-consumers of beer [ 122 ], but no estimation of phenols intake was performed, nor were consumption of alcohol-free beer nor spirits-only drinkers recorded. On the other hand, another observational study on the microbiota of 916 UK female twins found association only for wine drinkers but not for beer (nor all other alcohols) [ 123 ], but also in this case, the consumption of alcohol-free beer was not considered.…”
Section: Phenols-related Health Effects Of Beer Consumptionsupporting
confidence: 77%
See 1 more Smart Citation
“…As β-diversity was observed only after 30 days of treatment, the authors hypothesized that the effect on gut microbiota could depend on polyphenols and phenolic acids [ 111 ]. Similar results were obtained in an observational study, especially for higher butyric acid concentration in consumers versus non-consumers of beer [ 122 ], but no estimation of phenols intake was performed, nor were consumption of alcohol-free beer nor spirits-only drinkers recorded. On the other hand, another observational study on the microbiota of 916 UK female twins found association only for wine drinkers but not for beer (nor all other alcohols) [ 123 ], but also in this case, the consumption of alcohol-free beer was not considered.…”
Section: Phenols-related Health Effects Of Beer Consumptionsupporting
confidence: 77%
“…Non-alcoholic beer consumption also determines a positive modification of some parameters typical of metabolic syndrome such as glycemia and the β-cells’ function (AB1, drinkers of 355 mL/day of alcoholic beer; NAB, drinkers of 355 mL/day of non-alcoholic beer [ 111 ]). On the other hand, moderate beer consumption can increase the production of butyric acid, a fundamental molecule produced by the microbiota and useful for its healthy implications (AB2, drinkers of 200–600 mL/day; AO, abstainers or occasional consumers of <1.5 alcohol g/day [ 122 ]).…”
Section: Figurementioning
confidence: 99%
“…Samples were immediately frozen at −20 °C and transported on the next day in refrigerated conditions to the study center where they were stored at −80 °C until analyses. Starting from 180–220 mg of each fecal sample, bacterial DNA was extracted using an optimized protocol as described in Gonzalez-Zancada et al [ 24 ]. DNA was finally recovered with the commercial QIAamp DNA Fast Stool Mini Kit (QIAGEN GmbH, Hilden, Germany), following the manufacturer’s instructions and quantified using Nanodrop ND-1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…SCFAs are the primary products of microbial fermentation of undigested dietary carbohydrates especially acetate, propionate, and butyrate ( 24 ). Several reports highlighted the immunomodulatory capacities and the ability to strengthen epithelial barrier integrity ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%